2021
DOI: 10.1186/s12872-021-02119-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive crisis in patients with obstructive sleep apnea-induced hypertension

Abstract: Background Hypertensive crisis is an urgent/emergency condition. Although obstructive sleep apnea (OSA) in resistant hypertension has been thoroughly examined, information regarding the risk factors and prevalence of hypertensive crisis in co-existing OSA and hypertension is limited. This study thus aimed to determine prevalence of and risk factors for hypertensive crisis in patients with hypertension caused by OSA. Methods The inclusion criteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A first retrospective study describing comorbidities in Hungarian and Romanian OSA patients showed that various diseases such as cardiovascular diseases (e.g., hypertension and arrhythmias), diabetes, and asthma were strongly associated with OSA severity in the whole study population and that OSA-CIH played an important role in it [ 29 ]. Khamsai et al found that patients with OSA combined with hypertension were much more likely to develop hypertensive crisis than the general population [ 30 ], greatly increasing the risk of various cardiovascular and cerebrovascular diseases. It was also noted that carotid artery intima-media thickness and AS-related inflammatory markers were significantly increased in hypertensive patients with combined OSA, confirming the damage to the vascular endothelium caused by this pathological phenomenon [ 31 ].…”
Section: Dual Nature Of Ihmentioning
confidence: 99%
“…A first retrospective study describing comorbidities in Hungarian and Romanian OSA patients showed that various diseases such as cardiovascular diseases (e.g., hypertension and arrhythmias), diabetes, and asthma were strongly associated with OSA severity in the whole study population and that OSA-CIH played an important role in it [ 29 ]. Khamsai et al found that patients with OSA combined with hypertension were much more likely to develop hypertensive crisis than the general population [ 30 ], greatly increasing the risk of various cardiovascular and cerebrovascular diseases. It was also noted that carotid artery intima-media thickness and AS-related inflammatory markers were significantly increased in hypertensive patients with combined OSA, confirming the damage to the vascular endothelium caused by this pathological phenomenon [ 31 ].…”
Section: Dual Nature Of Ihmentioning
confidence: 99%
“…Consequently, the results may vary with the stage of COVID-19 outbreak and the method of data collection is based only on the responses to the developed questionnaire which cannot verify the truth of the answer. Note that no specific clinical risk factors are evaluated such as obstructive sleep apnea [17][18][19][20][21][22]. Finally, there might be might be cultural differences or norm with other population such as general population [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the outcomes were evaluated only at discharge and not over a longer term. Fourth, some factors possibly related to both stroke and atrial fibrillation were not examined such as laboratory tests and obstructive sleep apnea (25)(26)(27)(28)(29)(30)(31)(32)(33). Finally, authorization to access the database was only for the mentioned study period (2015-2017).…”
Section: Discussionmentioning
confidence: 99%